Signaling Pathways for Long-Term Memory Formation in the Cricket - Matsumoto, Yukihisa; Matsumoto, Chihiro S.; Mizunami, Makoto (Frontiers in Psychology, 2018)
Unraveling the molecular mechanisms underlying memory formation in insects and a comparison with those of mammals will contribute to a further understanding of the evolution of higher-brain functions. As it is for mammals, insect memory can be divided into at least two distinct phases: protein-independent short-term memory and protein-dependent long-term memory. We have been investigating the signaling pathway of long-term memory formation by behavioral-pharmacological experiments using the cricket Gryllus bimaculatus, whose olfactory learning and memory abilities are among the highest in insect species. Our studies revealed that the NO-cGMP signaling pathway, CaMKII and PKA play crucial roles in long-term memory formation in crickets. These long-term memory formation signaling pathways in crickets share a number of attributes with those of mammals, and thus we conclude that insects, with relatively simple brain structures and neural circuitry, will also be beneficial in exploratory experiments to predict the molecular mechanisms underlying memory formation in mammals.